The determinants of the customer's satisfaction towards Amassurance Berhad Sungai Petani / Fatimah Mohamed Tajuddin - Mohamed Tajuddin, Fatimah (Faculty of Business and Management, 2007)
In Malaysia, there are a lot of insurance companies that provide various products for the customers. Change to the customers lifestyles, improved living standard and the diversification of product requirement make the people need some covering for their future life if had some accidental situation happen. So this research is to collect the information about the customer's satisfaction towards the Amassurance company. So the Amassurance Berhad can take the action and respond with the desires of the customers and make them satisfied regarding to the products and services.